Novel agents may positively impact chemotherapy and transplantation in subsets of diffuse large B-cell lymphoma. Issue 6 (3rd June 2019) - Dahi, Parastoo B.; Moskowitz, Craig H.; Giralt, Sergio A.; Lazarus, Hillard M.
ABSTRACT: Introduction : Molecular and biologic heterogeneity in diffuse large B-cell lymphoma (DLBCL) has resulted in a broad range of clinical outcomes. While standard frontline chemoimmunotherapy cures majority of patients with DLBCL, treatment failure in certain DLBCL subsets remains high. Prognosis in these patients is dismal. Therefore, optimization of front-line therapy, as well as development of more effective salvage treatments, is an unmet medical need. Areas covered : This article reviews the treatment advances in DLBCL with novel and targeted agents that are aimed to improve efficacy especially in those with high-risk features. Expert opinion : Incorporation of novel therapies such as immunomodulatory agents and Bruton tyrosine kinase (BTK) inhibitors in the treatment of higher-risk DLBCL subgroups have shown to be effective; however, confirmatory data are required to change the standard of care. While autologous chimeric antigen receptor (CAR) T-cell therapy targeting CD19-positive B-cells have revolutionized the outcomes of refractory DLBCL, the complexity of its production, post-infusion care, and the associated cost, currently has limited its use to select academic centers in the US. A multitude of other targeted agents and combinations as well as cellular and immunotherapeutic agents are under investigation.